Bibliometric Analysis: STEM Research in High Schools (1988-2023) - Ilham Muhammad; Fadli Agus Triansyah (LPPM STKIP Kusuma Negara, 2023)
STEM, an educational model, equips gifted students with essential skills to foster creative problem-solving. The aim of this study was to capture the STEM-related landscape in high schools. The method used is bibliometric analysis. The data retrieved comes from the database Scopus. The results show that STEM-related publications in high schools continue to increase every year, especially from 2016 to 2021. Publications in 2011 have cited more than 160 citations, this number is more than any other year. Indonesia is the most influential country in this field. The focus of research related to this field is 1) outcomes and motivation; 2) critical thinking and 21st century; 3) problems and development. The new theme for this field is critical thinking, 21st century, project-based learning (PjBL), covid and perception. Keywords that become new themes such as critical thinking not yet connected directly with keywords with other new themes such as perception. Keywords that were the primary focus, such as motivation, outcomes, and STEM in high schools, did not directly align with the emerging theme of Covid. This novelty offers valuable insights for future research.